2022
DOI: 10.3389/fneur.2022.802554
|View full text |Cite
|
Sign up to set email alerts
|

Associations of the Severity of Obstructive Sleep Apnea With Age-Related Comorbidities: A Population-Based Study

Abstract: Aging is accompanied by changes in the quantity and quality of sleep. Obstructive sleep apnea (OSA) is also more prevalent in the older population. Although severe OSA has been linked to a higher risk of cardiovascular disease regardless of adult age, clinical consequences of mild-to-moderate OSA in the older adults are still uncertain.ObjectivesTo investigate the relationships between severity and metabolic, cognitive, and functional characteristics in community-dwelling older adults from a representative sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…These changes can lead to airway collapse, contributing to the development or worsening of sleep apnea ( Pham and Schwartz, 2015 ). The comorbidities increase the risk of developing sleep apnea in elderly ( Silva et al, 2022 ). Identifying risk factors for sleep apnea is of particular importance for the diagnosis of sleep apnea in the elderly ( Quinnell and Smith, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…These changes can lead to airway collapse, contributing to the development or worsening of sleep apnea ( Pham and Schwartz, 2015 ). The comorbidities increase the risk of developing sleep apnea in elderly ( Silva et al, 2022 ). Identifying risk factors for sleep apnea is of particular importance for the diagnosis of sleep apnea in the elderly ( Quinnell and Smith, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Modernity has brought many benefits and facilities to human life, but it was also accompanied by lifestyle changes such as reducing physical exercise and changing eating habits, contributing to the increase in the prevalence of cardiovascular diseases (CVD) and other metabolic disorders. The prevalence of sleep disorders has also increased, and many studies have found relationships between CVD, metabolic disorders, and sleep quality [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%